2022
DOI: 10.1088/1361-6382/ac5fc2
|View full text |Cite
|
Sign up to set email alerts
|

Extreme ℓ-boson stars

Abstract: A new class of complex scalar field objects, which generalize the well known boson stars, was recently found as solutions to the Einstein-Klein-Gordon system. The generalization consists in incorporating some of the effects of angular momentum, while still maintaining the spacetime's spherical symmetry. These new solutions depend on an (integer) angular parameter $\ell$, and hence were named $\ell$-boson stars. Like the standard $\ell=0$ boson stars these configurations admit a stable branch in the solution sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…These objects consider an additional harmonic decomposition in the rotation angle ϕ, Φ(r, t) = φ(r) e −i(ωt−lϕ) , (1.4) where l is an integer known as the azimuthal rotation number. As expected, rotating boson stars have non-zero angular momentum and greater complexities than their spherical siblings (notice that this is quite different from the -boson stars recently studied by Alcubierre et al [28], which are particular combinations of several scalar fields that result in spherical objects with non-zero total angular momentum). Rotating boson stars were first studied by Silveira and Sousa in Newtonian theory [29].…”
Section: Introductionmentioning
confidence: 70%
“…These objects consider an additional harmonic decomposition in the rotation angle ϕ, Φ(r, t) = φ(r) e −i(ωt−lϕ) , (1.4) where l is an integer known as the azimuthal rotation number. As expected, rotating boson stars have non-zero angular momentum and greater complexities than their spherical siblings (notice that this is quite different from the -boson stars recently studied by Alcubierre et al [28], which are particular combinations of several scalar fields that result in spherical objects with non-zero total angular momentum). Rotating boson stars were first studied by Silveira and Sousa in Newtonian theory [29].…”
Section: Introductionmentioning
confidence: 70%
“…A.1. Technical results for the Kottler solution In section 2.3 we present the result of the surface integral equation (15),…”
Section: Data Availability Statementmentioning
confidence: 99%
“…A similar effect, but in the strong gravity regime (beyond the weak field limit), is the strong lensing effect, which provides an experimental test for compact astrophysical objects, such as black holes, e.g. the one embedded in M87 galaxy [10] and SgrA* [11], or exotic ultracompact objects like boson stars [12,13], ℓ-boson stars [14][15][16][17], Horndeski stars [18,19], or other exotic compact objects such as superspinars, anisotropic stars, etc (see for example table 1 in [20]).…”
Section: Introductionmentioning
confidence: 99%
“…Anisotropic pressures are essential to obtain equilibrium configurations with high compactness and large values for the mass. In [35] (see [38] for recent discussion on fluid anisotropic stars and [39] for shell-type configurations in the Einstein-Vlasov system) it was shown that for ℓ-boson stars, small radial pressures and big tangential pressures are related to an increase in the mass and radius of the star in a way that resembles the forces on an arch. In our case, to understand the decrease in size of the magnetic boson stars, we start by noticing that the tangential pressure is composed by two different contributions, S θ θ and S ϕ ϕ , which act together with the radial pressure (and with the Lorentz force in some region) against gravity in order to support the configuration.…”
Section: Sequence Of Magnetic Boson Starsmentioning
confidence: 99%